2021
DOI: 10.21203/rs.3.rs-440254/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety and Depression in School-age Patients With Spinal Muscular Atrophy: a Cross-sectional Study

Abstract: Background: Spinal muscular atrophy (SMA) is a rare neurogenetic disease which involves multisystem dysfunctions such as respiratory, digestive, and motor disorders. Anxiety, depression and other psychological disorders often accompany severe chronic physical diseases. The aim of this study was to investigate the prevalence of anxiety and depression along with their influencing factors among school-age patients with SMA.Methods: We conducted a cross-sectional study on school-age SMA patients in China. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…As the disease progresses, it is often accompanied by multiple organ damage (9), which affects children's motor function, living activities, social participation, and even mental health. A mental health survey of 155 school-age children with SMA found that the incidences of anxiety and depression were 40.0% and 25.2%, respectively, and were significantly associated with caregivers' subjective anxiety (18). In addition, the mental health of the siblings and caregivers of SMA children can also be affected.…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, it is often accompanied by multiple organ damage (9), which affects children's motor function, living activities, social participation, and even mental health. A mental health survey of 155 school-age children with SMA found that the incidences of anxiety and depression were 40.0% and 25.2%, respectively, and were significantly associated with caregivers' subjective anxiety (18). In addition, the mental health of the siblings and caregivers of SMA children can also be affected.…”
Section: Discussionmentioning
confidence: 99%